Decision-making criteria for damage control surgery in Japan - Urushibata, Nao (Sci Rep, 2019)
Controversy still remains regarding the optimal criteria for selecting damage control surgery (DCS). Our objective was to propose an indication for implementing DCS for abdominal trauma requiring emergency laparotomy. This was a multicenter, retrospective, observational study that used data from the Japan Trauma Data Bank. Patients who underwent emergency laparotomy were included. We compared the patients regarding the performance of DCS. Of the 4447 patients included in the study, 532 patients were in the DCS group and 3915 patients were in the non-DCS group. Logistic regression analysis revealed that body temperature, level of consciousness (Glasgow Coma Scale), and type of injury (blunt or penetrating) were independent predictors of DCS. Using these predictors, we created the Damage Control Indication Detecting score. The score showed a positive correlation with mortality. The score was obtained as 5 of 9 points in total, revealing mortality of 30.8%, sensitivity of 64.8%, and specificity of 70.0%. The area under the curve for the receiver operating characteristic curve was 0.715. This score can help surgeons determine when to perform DCS. However, more than 95% of trauma cases in Japan involve blunt injuries, suggesting that the results of our study may not be applicable internationally.